Pneumoperitoneum, Pneumomediastinum and Subcutaneous Emphysema Following Diagnostic Colonoscopy - Antonio Palomeque Jiménez; Cristina González Puga; Beatriz Pérez Cabrera (Acta Médica Portuguesa, 2015)
Keywords: Colonoscopy/adverse effects; Mediastinal Emphysema; Pneumoperitoneum; Subcutaneous Emphysema.